DIFUSI INOVASI â€œBELANJA DARINGâ€ DI MEDIA SOSIAL DAN DAMPAKNYA PADA MOTIF BERBISNIS DI KALANGAN ANAK MUDA - Imam Nuraryo (Jurnal Manajemen, 2016)
This research used communication and marketing concept, marketing communication concept and Diffusion of Innovation Theory, which explain the process of how an innovation was encoded (communicated) through certain channels along a period of time to a community of a social system. The method in this research is quantitative. Researcher would be able to know whether there are any impacts of the diffusion of innovation for online shop on Facebook as the marketing communication in business. There were 100 respondents of college students. This research shows that as the communication media, Facebook impacts the business motivation of students with 35.5% simulators while the other 64.5% are the impacts of any other influencers that are not in the term of this research. The conclusion of this research is that only the variable of communication media/ channels significantly impacts the studentsâ€™ business motivation. Simultaneously proven, the Online Shopâ€™s diffusion of innovation through Facebook as the communication media has impacted the business motivation of students.   Keywords : Online Shopping, Marketing Communication, Diffusion Innovation